2021
DOI: 10.3390/ijms222111340
|View full text |Cite
|
Sign up to set email alerts
|

Tackling the Biological Meaning of the Human Olfactory Bulb Dyshomeostatic Proteome across Neurological Disorders: An Integrative Bioinformatic Approach

Abstract: Olfactory dysfunction is considered an early prodromal marker of many neurodegenerative diseases. Neuropathological changes and aberrant protein aggregates occur in the olfactory bulb (OB), triggering a tangled cascade of molecular events that is not completely understood across neurological disorders. This study aims to analyze commonalities and differences in the olfactory protein homeostasis across neurological backgrounds with different spectrums of smell dysfunction. For that, an integrative analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 57 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…They identified that the purine nucleoside phosphorylase (PNP) was the only over-expressed protein in AD, PD, MixD, and ALS. Thirteen OB proteins were differentially regulated in at least three neurological disorders, of which four of them (NCAM2, LY6H, COL6A3, and PRDX6) presented a homogeneous OB profile across diseases [ 41 ]. In addition, the epidermal growth factor receptor (EGFR) expression was significantly increased in the OB of AD and mixed dementia subjects [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…They identified that the purine nucleoside phosphorylase (PNP) was the only over-expressed protein in AD, PD, MixD, and ALS. Thirteen OB proteins were differentially regulated in at least three neurological disorders, of which four of them (NCAM2, LY6H, COL6A3, and PRDX6) presented a homogeneous OB profile across diseases [ 41 ]. In addition, the epidermal growth factor receptor (EGFR) expression was significantly increased in the OB of AD and mixed dementia subjects [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Still, it remains unclear which biochemical alterations cause the olfactory dysfunction in AD. Some authors propose SREBF1 and NFMUE1 (involving genes with 3′UTR containing motif CGGCCATCT) as transcription factors with a specific role of mediators relevant in AD olfactory neurodegeneration [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations